Research on coordination mechanism between agricultural green and land ecosystem in Yellow River Basin - Junjun Niu; Chunmei Mao (Scientific Reports)
Abstract The Yellow River Basin is China’s grain production base and ecological barrier, with an important strategic position. Therefore, it is of great significance to analyze spatiotemporal pattern of ecosystem services and agricultural green, and further exploring the driving mechanism of coordination using the GTWR model to examine how the Yellow River Basin’s agriculture evolve sustainably. The results indicate that: (1) In 2011–2021, the Yellow River Basin’s ecosystem service value showed a state of growth first and then decline, indicating that the decrease trend cannot be ignored; the Yellow River Basin has seen a steady rise in agricultural green level, with regional disparities progressively disappearing. (2) Although the Yellow River Basin’s agriculture and ecosystem has tended towards coordinated development, it was still in the primary stage of coordination; the tendency of downstream > midstream > upstream was seen in the notable geographical disparities, and the gap was continuously closing. (3) The harmonization of ecosystem service value and agricultural green development is driven by multiple factors. The influence of social factors has undergone a transition from negative influence to positive influence; economic factors generally had a positive impact, but there existed a certain amount of instability; the overall state of natural factors was relatively stable, with little change in areas with positive coefficients. In areas with negative coefficients, their negative effects gradually decreased and showed a trend towards positive development. In light of the finding above, some recommendations are put forth to promote sustainable agricultural production.